Człowiek w myśli Jana Pawła II - Nagy, Stanisław (Horyzonty Wychowania, 2017)
The aim of this article is presenting the understanding of the concept of „human being”. The author makes „John Paul II’s thought” the source of his reflection. The question: „who is man?” becomes the starting point of the deliberations. Firstly, he presents man as the subject dominating the world of objects. This term denotes man having the ability to learn the truth about the world in a special and specific way and, as a consequence, to learn the truth about himself (self-cognition). It also denotes man who is a separate being, having his own, distinct and unique personality. Secondly, he draws attention to man as a person and the resulting characteristics: his rationality, freedom, morality and consciousness. And thirdly, the author (following John Paul II) calls man a Christian. He claims that it is this „specification” of man as a person that determines his perspective, not only natural, but first of all supernatural. The key to such vision of man is Jesus Christ – the Redeemer, who as an example of man’s image by virtue of God’s nature being realised in Him and at the same time full human nature, fully reveals man to man himself and shows him his highest vocation. Man’s image understood and interpreted in this way leads to the necessity to discern dignity, greatness and full humanity he deserves by virtue of Redemption.